Liver Cancer - Sergi, Consolato M (Exon Publications, 2021)
Liver tumors are a heterogeneous and complex mix of benign and malignant neoplasms that may arise in the setting of chronic liver injury or due to no prior insult. In children, hepatoblastoma is the most common malignant primary liver tumor and hepatocellular carcinoma is rare. In adults, however, hepatocellular carcinoma is most common and undifferentiated embryonal sarcoma is vanishingly rare. Liver Cancer explores these, and the myriad of other entities in between, with a depth and precision that is highly informative and practical to the modern physician scientist. Descriptions of grossing techniques, histopathologic features, ancillary testing modalities, molecular/genetic abnormalities, imaging characteristics, treatment options, clinical signs/symptoms and surgical approaches are contemporary contributions to this exciting field. Liver Cancer represents the latest knowledge of primary liver tumors. Refreshingly, it focuses on tumors and underlying processes that affect both children and adults. Written by and for practicing Pathologists, Oncologists, Surgeons, Gastroenterologists and Radiologists, its comprehensive content makes it a valuable reference for primary liver tumors.